Discussion: Investigation on the Performance of a Mathematical Model to Analyze Concentrically Braced Frame Beams wtih V-Type Bracing Configurations - Roeder, Charles W.; Lehman, Dawn E.; Tan, Qiyang; Berman, Jeffrey W.; Sen, Andrew D. (Engineering Journal, 2021)
Discussion